Synthesis, characterisation, electrical and optical properties of copper borate compounds - Kipcak, Azmi Seyhun; Senberber, Fatma Tugce; Yuksel, Sureyya Aydin; Derun, Emek Moroydor; Piskin, Sabriye (PERGAMON-ELSEVIER SCIENCE LTD, 2015)
The hydrothermal synthesis of copper borate compounds [Cu(BO2)(2)] was studied, and several parameters were found to affect the synthesis. Raw materials, including CuSO4 center dot 5H(2)O, Na2B4O7 center dot 5H(2)O, Na2B4O7 center dot 10H(2)O, NaOH and H3BO3, were used. Reaction temperatures and reaction times between 40 degrees C and 100 degrees C and 15 and 240 min, respectively, were used. The as-synthesised copper borate was analysed using X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FT-IR) and scanning electron microscopy (SEM). The yields of the reactions were also calculated. Single-phase, nanoparticulate copper borate compounds (Cu(BO2)(2)) possessing high XRD crystal scores were obtained; the reactions used to obtain these materials were highly efficient. Electrical resistivity and optical absorbance measurements were carried out on the compounds obtained from the highest yielding reactions. The results of this study showed that even using a reaction time of 15 min, copper borate formation was successfully achieved. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Chemical synthesis; X-ray diffraction; Crystal structure; Electrical properties; Optical properties; MINE; Materials Science